Analizar una política pública mercosuriana: el caso del ejercicio profesional y la acreditación universitaria regional. - Solanas, Facundo (2014)
As regional integration processes are consolidated and societies become more complex, public policies are often crossed by new dimensions, scales, tensions and actions produced by different actors. In this sense, Mercosur and the public policies that are constructed in the block are realizing the existence of a new field for analysis. Based on case study of university's accreditation in the Mercosur, and relying on previous research carried out on the issue, we propose to study the concept of regional policy or "mercosuriana".